Effects of the stress hormone norepinephrine on the probiotic properties of Levilactobacillus: antibacterial colonization, anti-inflammation, and antioxidation - Niu, Lingdi; Gao, Mingchun; Li, Yifan; Wang, Chaonan; Zhang, Chuankun; Duan, Haoyuan; Li, Hai; Wang, Fang; Ge, Junwei (Frontiers in Microbiology, 2025)
Probiotics as antibiotic alternatives are unstable for use under stress in clinical applications. To explore the influence of catecholamine hormones on probiotic bacterial inhibition and antimicrobial activity, we tested the effects of norepinephrine (NE) on Levilactobacillus in vitro and in a mouse model. The in vitro results showed that in the presence of NE, 80% of Levilactobacillus strains showed increased growth rate and more than 80% of the strains indicated lower antimicrobial activity at 22 h. Furthermore, in the mouse model, NE weakens the protective effect of L. brevis 23,017 on Escherichia coli infection, which is shown by the decreased ability of antibacterial colonization, antioxidation, and anti-inflammation, and downregulating the expression of antioxidant genes and intestinal mucosal barrier-related genes. At the same time, the addition of NE modulates the bacterial microbiota richness and diversity in the intestine, disrupting the balance of intestinal probiotics. These findings provide evidence that NE reduces the probiotic ability of Levilactobacillus and illustrates the plasticity of the probiotics in response to the intestinal microenvironment under stress.